Lessons from Two Public Sector Reforms in Italy - Belhocine, Nazim (IMF Working Papers; Working Paper, 2020)
The reform of the Italian public administration has been a priority for at least two decades, with several major initiatives undertaken toward modernization and simplification. Notwithstanding laudable intentions, however, progress remains limited. This analysis is a case study of two reforms since 2016-on the rationalization of state-owned enterprises and of public procurement. It finds that original reform provisions were weakened or overturned, regulatory complexity and uncertainties in the application of the reforms blunted their impact, and enforcement mechanisms were inadequate. Addressing these gaps will be essential for successfully modernizing Italy's public administration.